Achievement Motivation and Competitive Anxiety Among Taekwondo Athletes: Motivasi Prestasi dan Kecemasan Kompetitif di Kalangan Atlet Taekwondo - Inggrit Oktavia; Ghozali Rusyid Affandi (Academia Open, 2025)
General Background: Psychological factors play a central role in shaping athletes’ competitive experiences, particularly in sports requiring high concentration and emotional regulation. Specific Background: In taekwondo competitions, achievement motivation and competitive anxiety frequently emerge as key psychological variables influencing athletes’ readiness before matches. Knowledge Gap: Although prior studies have examined motivation and anxiety separately, empirical evidence examining their relationship within regional taekwondo athlete populations remains limited. Aims: This study aimed to analyze the relationship between achievement motivation and competitive anxiety among taekwondo athletes. Results: The findings indicate a significant relationship between achievement motivation and competitive anxiety, demonstrating that variations in athletes’ motivational levels are associated with differences in their anxiety responses prior to competition. Novelty: This research provides empirical data within a specific taekwondo training context, contributing localized evidence to the field of sport psychology. Implications: The results highlight the importance of structured psychological preparation programs focusing on motivational development to help athletes manage competitive anxiety more effectively and support optimal performance readiness. Keywords: Achievement Motivation, Competitive Anxiety, Sport Psychology, Taekwondo Athletes, Quantitative Correlational Study Key Findings Highlights: Statistical analysis confirmed a significant association between motivational orientation and pre-competition nervousness. Athletes with stronger goal-driven tendencies demonstrated more controlled emotional responses before matches. Empirical data from a regional training context expand the current literature on psychological dynamics in combat sports.